Gestational age at birth, birth weight, and gestational age when intrauterine brain sparing occurs determines the neonatal outcome in growth-restricted infants born before 32 weeks of gestation: a retrospective cohort analysis - Köber, Franziska; Heimann, Yvonne; Lehmann, Thomas; Schleußner, Ekkehard; Proquitté, Hans; Groten, Tanja (Frontiers in Pediatrics, 2024)
Background: Preterm birth and fetal growth restriction are the main determinants of perinatal mortality. In the absence of therapeutic interventions, management is restricted to observation of fetal growth and fetoplacental perfusion to determine the timing of delivery. Fetal circulatory redistribution known as "brain sparing" represents a sign of fetal hypoxia and has been implemented in algorithms of when to deliver. In the absence of any other option the NO-donor pentaerithrityltetranitrate (PETN), which has been shown to improve fetoplacental flow and reduce preterm birth in high-risk patients, is offered to patients as personal therapy attempt. The aim of this study was to evaluate determinants related to pregnancy , including PETN intake during pregnancy, on immediate neonatal outcome in a cohort of growth restricted infants born before completed 32 weeks of gestation. Methods: We performed a retrospective cohort study of 98 infants born with a birth weight below the 10 th percentile before completed 32 weeks of gestation at our tertiary care center between 2010 and 2019. PETN was offered to all mothers with a history of severe adverse pregnancy outcome at high risk to develop fetal growth restriction as an individual therapy attempt. Results: Mean gestational age at birth was 188.5 days, mean birth weight was 549g corresponding to a median percentile of three. In 73 cases (79.3%), brain sparing occurred during pregnancy. 22 neonates (22.4%) were stillborn and 20 died postnatal, 37.3% developed a severe complication. Multivariable analysis revealed birth weight percentile, gestational age at birth and gestational age when brain sparing occurred first, as robust predictors of mortality or severe neonatal morbidity. In 39 neonates of mothers taking PETN this impact of brain sparing was not observed.Our study demonstrates is the first demonstrating a significant association of early occurrence of brain sparing with severe neonatal outcome in a cohort of very early preterm growth